Method for coating and forming renewable low-temperature SCR (Selective Catalytic Reduction) catalyst
By using thermoplastic as the carrier skeleton material, the preparation process is simplified and the pore structure is increased, which solves the problems of low mechanical strength, easy breakage and difficult regeneration of existing SCR catalysts, and realizes the efficient regeneration and environmentally friendly recycling of low temperature SCR catalysts.
Patent Information
- Application Number
- CN202510983339.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-11-07
AI Technical Summary
Existing SCR catalysts have complex preparation processes, low mechanical strength, are easily damaged, and are difficult to transport. Low-temperature denitrification catalysts are susceptible to SO2 poisoning, and their disposal costs are high and they pollute the environment. Furthermore, regeneration and recycling technologies are costly and inefficient, making it impossible to achieve economical and environmentally friendly circular use.
Thermoplastic plastics are used as the carrier skeleton material to prepare low-temperature SCR catalysts through thermoplastic molding process, which simplifies the preparation process, increases the pore structure, realizes the regeneration and recycling of catalysts, and improves the water poisoning resistance by using hydrophobic polymer materials.
It improves the mechanical strength of the catalyst, reduces the risk of damage during preparation and transportation, simplifies the regeneration process, reduces environmental pollution, achieves high yield and high recycling rate, and reduces production and regeneration costs.
Smart Images

Figure CN120900704A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of SCR catalysts, and in particular to a fine SCR denitration catalyst and system for nitrogen oxides (NO x ), a structure, configuration and corresponding process method.
[0002] More specifically, the present application relates to a method for coating and forming a regenerable low-temperature SCR catalyst. BACKGROUND
[0003] Nitrogen oxides (NO x ) are one of the most important atmospheric pollutants at present, and their excessive emission not only seriously threatens human health, but also causes a series of environmental problems. At present, the proportion of flue gas NO x emissions from non-electricity industries in China is increasing year by year, and achieving flue gas emission reduction in non-electricity industries is the focus of atmospheric pollution prevention and control work at the present stage.
[0004] Research and practice have found that ammonia-selective catalytic reduction (NH3-SCR) is the most mature technology for controlling NO x emissions at present, and is one of the best technologies for controlling NO x emissions, and the catalyst is the core of the SCR technology.
[0005] At present, the mainstream commercialized SCR denitration catalyst is a vanadium-based monolithic honeycomb catalyst (V2O5-WO3-TiO2), and its catalyst forming technology includes monolithic honeycomb forming, plate forming and corrugated plate forming, and is mainly prepared using titanium white powder as the paste material. Not only is the preparation process complex, but also it cannot tolerate errors. Once the forming process deviates from the optimal working condition of the forming process, the catalyst will be discarded because it cannot meet the use requirements. Moreover, the catalyst is prone to breakage during transportation, resulting in product loss. In addition, due to the large density of this type of vanadium-based catalyst, it is difficult to apply it in equipment scenarios such as ships and cars, which have strict requirements on the weight of the catalyst.
[0006] In addition, the desired denitration temperature of flue gas of large-scale non-fire power plant, cement kiln, industrial boiler and the like is mostly below 300°C. The existing low-temperature denitration catalyst is easily affected by fly ash, SO2, H2O and the like in the actual production operation process, leading to rapid deactivation of the catalyst and inability to be used normally for a long time. The used catalyst (which cannot meet the denitration requirements due to wear or deactivation and the like) is generally discarded directly, which not only wastes resources but also easily causes environmental pollution by being discarded at will. Although there are currently some studies on cleaning and regeneration of the catalyst, such as cleaning by ultrasonic cleaning and then acid / alkali washing and the like to restore the activity. However, in the production process of the existing technology, on the one hand, the cost of cleaning and regeneration of the catalyst is relatively high (about 40% of the price of a new catalyst, and the chemical life is 80% of that of a new catalyst), and the catalyst after multiple services cannot be recycled, which is not a recycling method with economic and environmental benefits. On the other hand, the chemical cleaning process generally inevitably causes pollution. In other words, the disposal and recycling of the catalyst also causes more costs, more complex post-treatment and more serious environmental pollution and the like.
[0007] The technology of loading a catalyst with a noble metal base by impregnation method, although it is beneficial to the recovery and utilization of the noble metal component to a certain extent, still has other losses in the extraction and filtration process, so that the noble metal active substance cannot be completely recovered. Moreover, the recovery process still causes a large amount of wastewater, some toxic gases and only a low recovery rate, and the process method needs to be further improved.
[0008] The existing vanadium-based catalyst (V2O5-WO3TiO2) has problems of complex preparation process (calcination for 20-30 days is required), low mechanical strength (easy to be broken during transportation), difficulty in regeneration (acid / alkali washing is required, and the cost is high) and environmental pollution and the like. In addition, the low-temperature denitration catalyst is easily poisoned by SO2 and H2O, and the disposal cost of the discarded catalyst is high and the environment is polluted.
[0009] The advanced preparation technology and regeneration technology of the industrial denitration catalyst after deactivation are still a big problem to be solved for the denitration catalyst at present.
[0010] In actual production and application of enterprises, the yield of catalyst preparation, breakage during transportation and deactivation of the catalyst in the actual working environment are difficult to avoid, and there is a long-term demand in the industry that the catalyst can be operated stably, with high performance and high reliability, for a longer time at a lower price. However, the current preparation and regeneration technology cannot make the catalyst have a relatively low operating cost and always maintain a relatively high catalytic activity.
[0011] Moreover, the spent catalysts cannot be easily disposed of in an environmentally friendly manner because they contain harmful substances such as heavy metals, which can easily enter the environment during loading, transportation, storage, and disposal, and then harm the environment and the health of living beings (including humans) through contact, inhalation, and food chain, and even cause cancer. Some spent catalysts also contain toxic components such as arsenic trioxide, arsenic pentoxide, chromium trioxide (as an example, not a common toxic component in denitration catalysts, can be replaced by vanadium pentoxide, a common component in denitration catalysts), and the like. If not properly disposed of, they will occupy space, pollute water and soil, release harmful gases, and increase air particulate matter. If properly disposed of to meet environmental and legal requirements, the high cost of materials, equipment, and processes required to dispose of the waste makes it essentially impractical for industrial use. The above chemical waste catalysts, including the above-mentioned spent catalysts, cannot be treated as general solid waste and must be entrusted to professional units with hazardous waste operating permits for recycling, utilization, and disposal to prevent environmental risks and ensure health and safety.
[0012] A Chinese patent application for invention with publication number CN117019136A, filed by the same inventor as this application on July 28, 2023, discloses a monolithic low-temperature manganese / cerium honeycomb denitration catalyst, which is prepared by using cerium dioxide (CeO2) and manganese oxide (MnO x ) as the main active components, titanium dioxide (TiO2) as the paste material, and adding a structure aid, and using an extrusion method. The catalyst was evaluated for catalytic activity and SO2 poisoning resistance by simulating the test environment of actual industrial flue gas. Experimental data show that the catalyst exhibits excellent low-temperature denitration activity and SO2 poisoning resistance, and can achieve removal of nitrogen oxides in low-temperature flue gas in actual industrial applications.
[0013] However, the existing catalyst preparation process uses inorganic materials such as TiO2 as the paste material, which is prone to sintering and will lose adhesion after multiple calcinations, making it impossible to use normally; the yield of the catalyst, damage during transportation, and deactivation of the catalyst in actual working conditions are difficult to avoid. The TiO2 material after multiple calcinations will reduce the mechanical strength of the formed catalyst and damage the structure, resulting in the catalyst being scrapped due to inability to use. Moreover, the mechanical strength of the catalyst prepared using TiO2 as the paste material is limited, and the catalyst is brittle, which can easily cause damage and breakage during transportation and use.
[0014] In addition, in the recycling and disposal of spent catalysts, such as catalyst regeneration and hazardous waste disposal, the recovery of active components from a large amount of TiO2 requires a large amount of energy, resulting in a large amount of energy waste and environmental pollution problems.
[0015] In summary, the catalyst regeneration and recycling treatment technology in the prior art has great difficulty, high cost, and poor technical effect and economic benefit, and therefore is not widely used and has a bleak prospect; the treatment of hazardous waste catalysts in the prior art is prone to cause resource waste and environmental pollution; the active substance extraction technology for recycling catalysts in the prior art, such as hydrometallurgy, pyrometallurgy and the like, has a complicated process, high energy consumption and long time consumption; the cleaning and active substance reloading (packing) of the catalyst during regeneration in the prior art not only has a complicated process step, but also greatly reduces the mechanical strength of the final regenerated catalyst product and the regenerated catalytic performance; the paste reshaping of the catalyst in the prior art in terms of regeneration and waste treatment affects the mechanical strength, and the hazardous waste needs special treatment.
[0016] Therefore, based at least on the above, there is a continuous need in the industry to innovate and create in the related preparation, material, structure, molding, regeneration and the like of the SCR catalyst, and to improve the existing catalyst molding and the like technical mode. It is desirable to innovatively improve or realize a repeatedly molded, conveniently post-processed and material recycled, regenerated and recycled molded catalyst and its preparation process, so as to alleviate or even overcome the defects of the prior art, and to achieve more beneficial technical effects and technical progress. SUMMARY
[0017] The present application is proposed in view of the above and other more ideas.
[0018] The inventors of the present application surprisingly found that the polymer (as a substrate / carrier / skeleton) supported catalyst can be regenerated and reused through research and repeated experiments and test verification. The present application proves that the polymer substrate (or carrier / skeleton) supported catalyst can be regenerated through a simplified reshaping process suitable for industrial scale production, realizes multiple use, greatly reduces material and production costs, and greatly reduces or even substantially eliminates negative impacts on the environment.
[0019] One of the purposes of the present application is to provide a method for coating and molding a regenerable low-temperature SCR catalyst, which uses a thermoplastic plastic as a carrier skeleton and contains a low-temperature SCR catalytically active component dispersed and supported in the carrier skeleton formed by the thermoplastic plastic. The method of the present application aims to realize the preparation, reshaping and regeneration of the low-temperature SCR catalyst through a coating and molding process.
[0020] The inventors of the present application have surprisingly found that the present application can use a thermoplastic catalyst molding process, using thermoplastic materials instead of TiO2or the like as the skeleton (carrier) material of the catalyst; at the same time, the powder catalyst component can be used as a binder for thermoplastic materials to help the various components / structures of the molded thermoplastic-based SCR catalyst to be better bonded and combined together. Ultimately, through the concept and technology of the present application, the powder catalyst thermoplastic is first molded and repeatedly molded into an industrial-grade catalyst with substantially stable and unchanged catalyst activity, stable surface physical and chemical properties, strong and light, and can be repeatedly molded and regenerated, which can replace the existing low-temperature denitration catalyst, and can be applied to a wide range of applications, including ships, automobiles, thermal power plants, incineration plants, cement plants, gas scrubbing equipment, etc. that require lightweight catalysts.
[0021] According to an aspect of the basic application concept of the present application, a low-temperature SCR catalyst is provided, in which thermoplastic is used instead of conventional carrier materials such as TiO2as a conventional skeleton (carrier) material, the manufacturing process is simplified through molding processes such as thermoplastic / thermoforming / extrusion, etc., and the pore / channel structure of the catalyst can be selectively increased by using a pore-forming agent. The low-temperature SCR catalyst can be regenerated by remolding after being broken after deactivation, achieving regeneration and recycling.
[0022] Some important aspects of the inventive concept of the present application are further described as follows:
[0023] (1) Thermoplastic can be used instead of conventional carrier materials such as TiO2as a catalyst carrier skeleton material, simplifying and facilitating the catalyst manufacturing process and regeneration process.
[0024] The industrial denitration (nitrogen oxides (NO xThe catalyst generally uses TiO2 and other materials as the main paste material, and the active component is mixed into the mud during the molding process or is impregnated into the support material after the preparation of the support material is completed, and then the finished catalyst is obtained after calcination and cutting processing. The calcination process can cause the active substance to precipitate from the solution, and can also cause the support material to sinter and thus be more tightly bonded together. The production of a batch of catalysts requires processes such as mixing, mud preparation, aging, extrusion, drying, calcination, and cutting, which takes about 20-30 days. The present application uses thermoplastic plastic as a carrier skeleton material instead of the existing process, which only needs to mix thermoplastic powder and catalyst powder, and then perform a thermoplastic process in a mold. Due to the special surface properties of the plastic material, there is almost no mold sticking, and the desired monolithic catalyst material can be obtained from the raw materials in a very short time. The preparation by hot pressing method requires even shorter time. Moreover, the method disclosed in the present application is limited by the hot melting temperature of the plastic material, which is lower than the calcination forming temperature of TiO2 material and requires shorter heating time, without the need for a drying process, and the integrated rapid forming.
[0025] (2) The low-temperature denitration catalyst is loaded on the polymer material (i.e. thermoplastic plastic material) to perform integrated monolithic molding, thereby improving the mechanical strength of the monolithic catalyst.
[0026] The traditional process for preparing industrial catalysts generally uses TiO2 and other materials as the main paste material, which has a certain mechanical strength. However, different denitration catalysts use different active components, and the addition of active components can improve the catalytic activity of the catalyst, but too much active component can reduce the adhesion of the TiO2 paste, leading to embryo breakage, damage, and other problems during the drying process. Even if there is no breakage or cracking during the preparation process, there is still a probability of catalyst breakage and damage after calcination due to uneven heating and excessive active component in some areas. More likely, the catalyst prepared from TiO2 and other materials is prone to crushing and collision during transportation, resulting in breakage and damage. In addition, catalysts with insufficient mechanical strength can also collapse and break due to excessive flue gas flow rate during use, which can no longer be used.
[0027] The preparation method using thermoplastic plastic as a carrier skeleton material introduced in the present application can use thermoplastic plastic material as the main body of the catalyst, which has stable physical and chemical properties and excellent mechanical strength. The catalyst can maintain the integrity of the catalyst during normal transportation and use, and can withstand greater flue gas pressure drop. Moreover, the preparation process does not require long-time drying and calcination, but only one thermoplastic process, which greatly simplifies the process flow, reduces the possibility of low yield caused by the process flow, and allows waste catalysts caused by misoperation to be remolded, saving resources.
[0028] In addition, various thermoplastics can be used to support the catalyst material stably and smoothly because their softening temperatures are higher than the working temperature window of the catalyst.
[0029] (3) The addition of pore-forming agents provides more pore structures for the catalyst
[0030] During the thermoplastic molding process, bubbles and cavities are generated due to uneven heating in the mold, which is undesirable in the preparation of plastic parts, but is desirable in the preparation of catalysts. The bubbles and channel structures can effectively increase the specific surface area and expose more active sites of the catalyst, thereby improving the catalytic activity. On this basis, we added pore-forming agents during the thermoplastic process and increased the water washing / solution immersion process to remove them (e.g., by dissolution), so that the final product can have more pore structures.
[0031] (4) Simplify the catalyst regeneration process and make the catalyst recyclable.
[0032] The main reasons for catalyst deactivation are fly ash blocking the catalyst pores and the catalyst being affected by SO2 and H2O, which leads to catalyst deactivation. For deactivated catalysts, we can simply clean them by washing off the fly ash and deposited ammonium sulfate salt components on the surface of the catalyst, then physically crush the shaped catalyst into powder, and then perform the thermoplastic molding process again. During the crushing process, all the crushed powder samples are collected, and during the reshaping process, only a small amount of catalyst powder needs to be added. After reshaping, the sample size hardly changes, the catalytic activity does not decrease, and the catalyst can almost be recycled.
[0033] (5) Change of substrate material to make the catalyst resistant to water poisoning.
[0034] Polymer materials can be used as catalyst carriers to solve the problem of water poisoning due to their stable physical and chemical properties and non-wetting surfaces. In other catalytic reactions, polymer substrates can effectively promote the rapid departure of water and improve reaction activity. Physical mixing of catalyst powder and hydrophobic polymer materials has been proven to improve the water poisoning resistance of the catalyst. This application uses thermoplastics as catalyst carrier materials. After the catalyst powder and thermoplastics are thoroughly mixed, for example, thermoplastic molding, there may be an immersion process during preparation, but it does not affect the catalytic activity of the catalyst because the hydrophobic polymer matrix material makes the catalyst have good water poisoning resistance.
[0035] According to the concept of one aspect of the present application, there is provided a method for coating and forming a regenerable low-temperature SCR catalyst, the low-temperature SCR catalyst comprising: a carrier skeleton; a low-temperature SCR catalytically active component coating coated on the thermoplastic carrier skeleton, the low-temperature SCR catalytically active component coating being formed by a thermoplastic emulsion solidified on the carrier skeleton after coating, wherein the thermoplastic emulsion comprises SCR catalytically active component powders dispersed therein; the method comprising the following steps: (1) adding the SCR catalytically active component powders into the thermoplastic emulsion for stirring and dispersing treatment; (2) coating the thermoplastic emulsion containing the dispersed SCR catalytically active component powders on the carrier skeleton; (3) drying treatment and optional further processing of the coated carrier skeleton, to obtain a formed low-temperature SCR catalyst, wherein the formed low-temperature SCR catalyst is capable of being regenerated by re-forming.
[0036] According to one embodiment, the carrier skeleton is a thermoplastic carrier skeleton.
[0037] According to one embodiment, the thermoplastic of the carrier skeleton has the same plastic component as the thermoplastic emulsion.
[0038] According to one embodiment, the carrier skeleton is a metal carrier skeleton or an inorganic non-metal carrier skeleton.
[0039] According to one embodiment, the carrier skeleton has at least one shape selected from the group consisting of a sheet shape, a flat plate shape, a corrugated plate shape, a cloth shape, a tubular shape, a granular shape, a mesh shape, a honeycomb shape, and a porous sponge shape.
[0040] According to one embodiment, the method is applicable to at least one of PEEK, PFA, PPS, PTFE, PBT, PEI, PES, PCTFE, ETFE, PAI, PBI, PI, FEP, PPA, PSU, PPSU, PE, PP, fluoro rubber (FKM), silicone rubber (VMQ), and nylon (PA) as the thermoplastic of the carrier skeleton.
[0041] According to one embodiment, the method further comprises the step of coating a thermoplastic emulsion containing SCR catalytically active component powders on the carrier skeleton after re-forming the carrier skeleton of the deactivated low-temperature SCR catalyst to regenerate the low-temperature SCR catalyst.
[0042] According to one embodiment, the re-forming comprises re-forming after crushing the deactivated low-temperature SCR catalyst.
[0043] According to an embodiment, the re-shaping comprises adding, in the deactivated low-temperature SCR catalyst after pulverization, a thermoplastic plastic powder, and at least one of a pore-forming agent, a foaming agent and a plasticizer.
[0044] According to an embodiment, the method further comprises: after separating the coating layer of the SCR catalytically active component of the deactivated low-temperature SCR catalyst, adding, in the coating layer, a thermoplastic plastic and at least one of a pore-forming agent, a foaming agent and a plasticizer, and forming a regenerated mixed powder after pulverization treatment; and re-shaping the regenerated mixed powder to obtain a regenerated low-temperature SCR catalyst.
[0045] The re-shaping is selected from at least one of the following processes: thermoplastic forming, hot-press forming, extrusion forming, 3D printing forming, electrostatic spinning forming, injection molding forming, die molding forming, blow molding forming, calendering forming, rotational molding forming, suction molding forming, slush molding forming, flow casting forming, foaming forming, transfer molding forming and winding forming.
[0046] According to an embodiment, the carrier skeleton has a self-supporting configuration before the re-shaping and after the re-shaping coating processing, so that the low-temperature SCR catalyst has a self-supporting configuration without external support in a set working temperature range.
[0047] According to an embodiment, the method further comprises a step of cleaning the deactivated low-temperature SCR catalyst before the re-shaping.
[0048] According to another aspect of the present application, a low-temperature SCR catalyst capable of being re-shaped and regenerated is provided, the low-temperature SCR catalyst comprising: a carrier skeleton of thermoplastic plastic, wherein the shape of the carrier skeleton of thermoplastic plastic is selected from at least one of a flat plate shape, a corrugated plate shape, a honeycomb shape, a granular shape, a cloth shape, a tubular shape, a rod shape, a mesh shape and a porous sponge shape; and a low-temperature SCR catalyst active part complexed on or in the carrier skeleton and supported thereby; wherein the low-temperature SCR catalyst is capable of being regenerated by re-shaping of the carrier skeleton of thermoplastic plastic into one of a flat plate shape, a corrugated plate shape, a honeycomb shape, a granular shape, a cloth shape, a tubular shape, a rod shape, a mesh shape and a porous sponge shape.
[0049] According to an embodiment, the low-temperature SCR catalyst active part comprises a low-temperature denitration catalytically active material.
[0050] According to an embodiment, the low-temperature denitration catalytically active material comprises at least one of a Mn / Ce catalytic material, a V-based catalytic material or a Cu-based catalytic material.
[0051] According to an embodiment, the carrier skeleton has an internal porous structure.
[0052] According to an embodiment, the internal porous structure occupies more than 10% of the volume percentage of the carrier skeleton.
[0053] According to an embodiment, the low-temperature SCR catalyst active part is compounded in the carrier skeleton in the form of dispersed particles.
[0054] According to an embodiment, the low-temperature SCR catalyst active part is compounded on the carrier skeleton in the form of a thin film.
[0055] According to an embodiment, the working temperature of the low-temperature SCR catalyst is below 300°C.
[0056] According to an embodiment, the thermoplastic plastic is selected from at least one of PEEK, PFA, PPS, PTFE, PBT, PEI, PES, PCTFE, ETFE, PAI, PBI, PI, FEP, PPA, PSU, PPSU, PE, PP, fluororubber (FKM), silicone rubber (VMQ), and nylon (PA).
[0057] According to an embodiment, the carrier skeleton of the low-temperature SCR catalyst has a self-supporting configuration before reshaping and after reshaping, thereby making the low-temperature SCR catalyst have a self-supporting configuration without external support in a set working temperature range.
[0058] The present application overcomes many inherent technical defects of the conventional technology, including: overcoming the great waste and high cost of catalyst modules caused by the easy deactivation, inability to reshape and regenerate of the conventional catalyst / modules; the environmental negative impact and environmental pollution caused by the disposal of conventional catalyst / modules; overcoming the length, complexity and high cost of the conventional production process and steps of conventional catalyst / modules; the lightweight catalyst modules of the carrier material of the present application replacing the cumbersome conventional catalyst / modules, reducing the difficulty of disassembly and transportation of conventional catalyst / modules, etc.
[0059] The present application can also achieve other advantageous technical effects not listed one by one, some of which are described below, and which can be expected and understood by those skilled in the art after reading the present application. BRIEF DESCRIPTION OF DRAWINGS
[0060] The above-mentioned features and advantages of the embodiments, as well as other features and advantages of the embodiments, and the manner of realizing them, will become more apparent, and the embodiments of the present application can be better understood, by reference to the following description taken in conjunction with the accompanying drawings. Brief description of the drawings is as follows.
[0061] Figure 1A and Figure 1BThese are, respectively, honeycomb catalyst products and granular catalyst products prepared by thermoplastic molding according to an embodiment of this application.
[0062] Figure 2A and Figure 2B These are three-dimensional schematic diagrams of industrial products of plastic honeycomb catalysts prepared by thermoplastic molding, for example, according to an embodiment of this application. Figure 2A ), and cross-sectional schematic diagram ( Figure 2B ),in Figure 2B The diagram schematically illustrates the presence of numerous pore structures in the flue gas channels of this thermoplastic honeycomb catalyst product.
[0063] Figure 3A A front view photograph of a plate-shaped catalyst product prepared by hot pressing according to an embodiment of this application is shown.
[0064] Figure 3B A perspective view of a thermoplastic plate catalyst product prepared by hot pressing according to an embodiment of this application is schematically shown.
[0065] Figure 3C schematically shown Figure 3A The image shown is an enlarged schematic of a single thermoplastic plate catalyst product, demonstrating the presence of numerous porous structures on the surface of the plate catalyst.
[0066] Figure 4 A schematic diagram of an activity evaluation apparatus for testing and evaluating the catalytic activity of the honeycomb low-temperature SCR catalyst of this application is shown.
[0067] Figure 5 This illustration schematically demonstrates a performance comparison between a PEEK-based catalyst prepared by thermoplastic molding according to an embodiment of this application and an industrial catalyst.
[0068] Figure 6 The illustration schematically shows a performance comparison between PEEK, PFA, and PPS-based catalysts prepared by thermoplastic molding according to an embodiment of this application and industrial catalysts.
[0069] Figure 7 The illustration schematically demonstrates a performance comparison of different plastic-based catalysts prepared by hot pressing according to an embodiment of this application.
[0070] Figure 8 The SO2 poisoning performance test results of a PEEK-based catalyst according to an embodiment of this application and the SO2 poisoning performance test results of a PEEK-based catalyst after deactivation and re-forming are illustrated schematically.
[0071] Figure 9Data showing the performance recovery of a PEEK-based catalyst according to an embodiment of the present application after SO2 poisoning and regeneration is schematically illustrated.
[0072] Figure 10 Data showing the performance test results of a PEEK-based catalyst according to an embodiment of the present application after multiple reforming of the PEEK-based catalyst and operating the PEEK-based catalyst at a predetermined reasonable operating temperature is schematically illustrated.
[0073] Figure 11 An example of a thermoforming process for preparing a low temperature SCR catalyst according to an embodiment of the present application by a thermoforming process is schematically illustrated.
[0074] Figure 12 An example of a coating forming process for preparing a low temperature SCR plate catalyst according to an embodiment of the present application by a coating forming process is schematically illustrated.
[0075] Figure 13 An example of a multiple regeneration capable fine SCR DeNOx catalyst system according to an embodiment of the present application is schematically illustrated for the purpose of schematically illustrating and describing the system and its general configuration of the segmented catalyst (module / segment) arrangement for fine SCR DeNOx according to the present application. DETAILED DESCRIPTION
[0076] The details of one or more embodiments of the application are set forth in the description below. Other features, objects, and advantages of the application will be apparent from the description and drawings, and from the claims.
[0077] It should be understood that the illustrated and described embodiments are not limited in application to the details of construction and arrangement of parts shown and described in the following description or illustrated in the drawings. The illustrated embodiments can be one of many embodiments and can be practiced or carried out in various ways. Indeed, it will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments / examples of the application without departing from the scope or spirit of the application. For instance, features illustrated or described as part of one embodiment, can be used with another embodiment to yield still a further embodiment. Thus, it is intended that the present disclosure cover such modifications and variations of this application provided they come within the scope of the appended claims and their equivalents.
[0078] Also, it is to be understood that the phraseology and terminology used herein is for the purpose of description and should not be regarded as limiting. The use of "including," "comprising" or "having" and variations thereof herein is meant to encompass the items listed thereafter and equivalents thereof as well as additional items.
[0079] The application will be described in greater detail with reference to several specific embodiments of the application.
[0080] Generally speaking, the working principle of selective catalytic reduction (SCR) de-NOx catalyst mainly involves the following steps:
[0081] (i) External diffusion process: the process of diffusion of nitrogen oxides and ammonia from the gas phase bulk to the outer surface of the catalyst;
[0082] (ii) Internal diffusion process: diffusion of the reactants from the outer surface to the inner surface of the catalyst so that the reaction occurs at the active center;
[0083] (iii) Adsorption process: adsorption of the reactants at the active center;
[0084] (iv) Catalytic reaction: catalytic reduction reaction of the adsorbed nitrogen oxides (NO x ) and ammonia at the active center of the catalyst and at a certain temperature to generate nitrogen and water;
[0085] (v) Desorption process: desorption of the reaction products from the active center; and
[0086] (vi) Internal diffusion process: diffusion of the reaction products from the active center to the outer surface of the catalyst through the inner surface of the catalyst after desorption.
[0087] Low-temperature SCR de-NOx systems generally include a device for storing and injecting a reducing agent such as ammonia NH3 or urea CO(NH2)2, an SCR control unit, and an SCR catalyst. Urea is hydrolyzed and decomposed to generate ammonia. At a suitable low-temperature condition (generally about 200-300°C or below), an ammonia-selective catalytic reduction (NH3-SCR) agent can directly catalyze the reaction of nitrogen oxides (NO x ) in flue gas with ammonia to generate harmless nitrogen and water, while absorbing harmful flue gas particles. The corresponding reaction formula is as follows:
[0088] CO(NH2)2+ H2O = CO2↑+ 2NH2↑
[0089] 4NH3+ 4NO + O2= > 4N2+ 6H2O
[0090] 4NH3+ 2NO2+ O2= > 3N2+ 6H2O
[0091] In terms of conventional technology, TiO2-based catalysts gradually replace Pt-Rh and Pt series catalysts. The composition of such catalysts has V2O5 as the main active component and WO3, MoO3 as the anti-oxidation and anti-poisoning auxiliary components, for example, mainly composed of V2O5(WO3), Fe2O3, CuO, CrO x , MnO xMetal oxides such as TiO2, Al2O3, ZrO2, SiO2, activated carbon (AC), etc. or a mixture thereof as a carrier, and a reducing agent such as liquid ammonia or urea in the SCR system to form a reducing reaction, which is the mainstream catalyst product for the SCR denitration project in power plants.
[0092] The inventors of the present application found that in the field of catalysts, polymer-supported nanocatalyst particles as carrier materials can be regenerated and reused, which makes it possible for the nanocatalyst particles after service to be regenerated and reused in new or regenerated catalysts. This recyclable feature makes it possible for the pollutants generated during the production of catalysts not to flow back into the environment to cause pollution. The organic polymer carrier (or base, skeleton, etc.) of the catalyst has a relatively low degree of active site exposure due to its small surface area, and therefore needs to add other aids to help generate a large number of pore structures to increase its specific surface area. In addition, this method accelerates the diffusion of water out of the catalyst, which helps to improve the activity and long-term stability of the catalyst.
[0093] One of the main ideas of the present application is to use a hydrophobic organic polymer, especially a hydrophobic thermoplastic, as the carrier skeleton of a low-temperature SCR catalyst. On the one hand, it can achieve the above technical advantages and be technically applicable to the application of low-temperature SCR catalysts (here, "low temperature" refers to the normal working temperature of the SCR catalyst, which is generally below 300°C, and more preferably below 250°C). On the other hand, the thermoplasticity of such plastics makes it possible to scale the reforming and regeneration process of the low-temperature SCR catalyst.
[0094] Of course, those skilled in the art can understand that using thermoplastic plastics (such as but not limited to PPS, PEEK, PBT, etc.) as low-temperature SCR catalyst carrier / base materials can achieve more technical advantages and benefits, including but not limited to: easy cleaning, crushing, processing and reforming after sulfur (e.g., SO2) poisoning and deactivation (ammonium sulfate deposition); can be easily used in a wide range of application environments including low ash areas, and is easy to clean and regenerate; the characteristics of thermoplastic plastics make the low-temperature SCR catalyst product lightweight, easy to transport and install, and less brittle, which is not easy to damage during transportation, installation and use; wide availability, easy availability and low cost of materials; non-toxicity and environmental friendliness of materials; extremely high yield (theoretical yield 100%, no inferior products); extremely high recycling rate (theoretical recycling rate close to 100%).
[0095] The inventors of the present application have found that the carrier / base material suitable for low-temperature SCR catalysts can be selected to use a thermoplastic plastic material with relatively high plasticizing forming temperature (e.g. its forming temperature is generally above about 200℃) as the carrier skeleton forming agent, such as but not limited to PBI; PI; TPI; PAI; PEEK; PPS; PTFE; PFA; ETFE; PCTFE, etc. The normal working temperature of such thermoplastic plastic-based “low-temperature” SCR catalyst is generally below 300℃, more preferably below 250℃.
[0096] The forming process of thermoplastic plastic material in the preparation of low-temperature SCR catalysts of the present application can include but is not limited to: thermoforming, hot-press forming, extrusion forming, 3D printing forming, electrostatic spinning forming, spray forming, injection forming, die forming, blow forming, calendering forming, rotational molding forming, vacuum forming (suction forming), casting forming (injection forming), slush molding forming, flow forming, foaming forming, transfer molding forming (compression molding), winding forming, etc.
[0097] The shape (configuration) of the low-temperature SCR catalysts of the present application after preparation can include but is not limited to: honeycomb catalyst products, plate catalyst products, corrugated plate catalyst products, tubular catalyst products, rod catalyst products, granular catalyst products, mesh catalyst products, porous solid foam catalyst products, etc. According to the above concepts and features of the present application, these catalyst products can be reformed and regenerated after use.
[0098] According to the concept of one aspect of the present application, the thermoplastic forming of the low-temperature SCR catalysts of the present application can effectively perform rapid thermoplastic forming with polymeric thermoplastic plastic as the carrier material of the catalyst; the combination effect is better after adding catalyst powder (which can act as a binder), and the forming effect is better; the large number of pore structures generated during the thermoplastic process can make the formed catalyst have a larger specific surface area, thereby improving the catalytic activity; the performance of the catalyst is directly related to the content of the catalyst during the forming process, and the thermoplastic formed low-temperature SCR catalysts of the present application have a larger proportion of catalyst components, so their catalytic performance is better than existing catalysts under the same test conditions.
[0099] The thermoplastic polymer materials suitable for the low-temperature SCR catalysts of the present application in thermoplastic forming and extrusion forming include: PEEK, PFA, PPS, PTFE, PBT, PEI, PES, PCTFE, ETFE, PAI, PBI, PI, FEP, PPA, PSU, PPSU, PE, PP, fluororubber (FKM), silicone rubber (VMQ), nylon (PA), etc. These materials are all polymer materials with rapid thermoplastic ability and stable physical and chemical properties.
[0100] In the present embodiment, the catalyst powder used is selected from catalyst materials with good low-temperature denitration performance, such as: Mn / Ce low-temperature denitration catalyst, V-based catalyst, Cu-based catalyst, and the like.
[0101] For detailed introduction of the Mn / Ce low-temperature denitration catalyst and related content of the formula, please refer to the Chinese patent application for invention CN117019136A filed by the inventor of the present application on July 28, 2023, which is incorporated herein by reference.
[0102] Examples of low-temperature SCR catalysts
[0103] Figure 1A and Figure 1B and Figure 2A and Figure 2B The present application illustrates the catalyst product prepared by the thermoplastic molding method. Among them, Figure 1A and Figure 1B are respectively the honeycomb catalyst product and the granular catalyst product prepared by the thermoplastic molding method according to an embodiment of the present application. Figure 2A and Figure 2B are respectively the perspective view ( Figure 2A ) and the cross-sectional view ( Figure 2B ) of the plastic honeycomb catalyst industrial product prepared by the thermoplastic molding method according to an embodiment of the present application, wherein Figure 2B illustrates that there are a large number of pore structures in the flue gas channel of the thermoplastic honeycomb catalyst product, which are formed by the added pore-forming agent. Those skilled in the art can understand that, as mentioned above, the preparation of the low-temperature SCR catalyst (including but not limited to honeycomb) mentioned in the present application can also be implemented by other molding processes disclosed in the present application, such as coating molding process, and is not limited to thermoplastic molding, hot-pressing molding.
[0104] Thermo-plastic forming of low-temperature SCR catalysts
[0105] Figure 11 The present application illustrates the thermoplastic molding process example of preparing the low-temperature SCR catalyst of the present application according to an embodiment of the present application.
[0106] The following takes PEEK material as an example, and further introduces the thermoplastic molding process method of the low-temperature SCR catalyst of the present application in combination with the attached Figure 11 .
[0107] 1) Mix 200 mesh Mn / Ce catalyst powder (8 parts by weight) with PEEK powder (20 parts by weight), add NaCl, CaSO4, (NH4)2CO3, carbon powder, etc. as pore-forming agents (10 parts by weight), mix thoroughly, and place in a cylindrical stainless steel mold.
[0108] 2) Seal the stainless steel mold with a stainless steel press, place in a muffle furnace, and plasticize and form at 300-320°C under a pressure of about 10.0 MPa for 6 hours.
[0109] 3) After water cooling, soak for 1-24 hours to remove the pore-forming agents, dry to obtain a cake-shaped thermoplastic formed catalyst, and perform punching processing on the obtained catalyst on a numerical control machine to obtain a honeycomb-shaped low-temperature SCR catalyst product, such as shown in Figure 1A and Figure 2A and Figure 2B .
[0110] Hot-press forming of low-temperature SCR catalysts
[0111] Figure 3A A front view photo of a plate-shaped catalyst product prepared by a hot-press forming method according to an embodiment of the present application is shown. Figure 3B A perspective view schematic diagram of a thermoplastic plate-shaped catalyst product prepared by a hot-press forming method according to an embodiment of the present application is shown schematically. Figure 3C A photo of a single thermoplastic plate-shaped catalyst of the thermoplastic plate-shaped catalyst product shown in Figure 3A , showing that a large number of pore structures exist on the surface of the plate-shaped catalyst.
[0112] The thermoplastic polymer materials suitable for use in hot-press forming of the low-temperature SCR catalyst of the present application include: ETFE, PFA, FEP, PPS, PBT, PBI, PEI, PSU, PEEK, fluororubber (FKM), silicone rubber (VMQ), nylon (PA), etc. These polymer materials are all materials having a suitable softening temperature, almost no flow in a molten state, good surface wettability, and stable physical and chemical properties.
[0113] Coated forming of low-temperature SCR catalysts
[0114] Figure 12 An example of the coating forming process step for preparing the low-temperature SCR plate-shaped catalyst of the present application according to a coating forming method according to an embodiment of the present application is shown schematically.
[0115] A thermoplastic emulsion (or powder) such as FEP emulsion with 20% FEP content (mass) is weighed 1 part, optionally, NaCl crystal (as a pore forming agent) with 1 part of mass is added, and the mixture is stirred until the NaCl crystal is almost completely dissolved. The resulting mixture is added to a catalyst powder with 1 part of mass, and the mixture is stirred for 10-15 minutes to obtain FEP paste for coating and molding.
[0116] The FEP paste is coated on a 80 mesh metal screen to obtain a coated sheet metal. The coated sheet metal is placed in an oven at 100°C for 15 minutes to ensure that the NaCl crystal as a pore forming agent is completely precipitated. The metal sheet is then placed in an oven at 260°C for 20-30 minutes. The coating process is repeated several times, for example, more than 3 times.
[0117] As an alternative to the skeleton, a thermoplastic plastic can be used as a skeleton, including but not limited to FEP plastic skeleton, instead of 80 mesh metal screen. For example, alternatively, the FEP paste can also be coated on a mesh, plate, or porous plate FEP plastic skeleton at least once, and if a pore forming agent is added, an alternative precipitation process can be performed.
[0118] After the washing process, the NaCl crystal occupying the pore structure is washed away, and the coated and molded plate (plate) low-temperature denitration catalyst is obtained after drying.
[0119] The coated and molded plate low-temperature denitration catalyst will be deactivated after a period of low-temperature denitration catalytic work. The coated and molded plate catalyst that has been deactivated is subjected to catalyst layer peeling (for example, by mechanical peeling, chemical peeling, ultrasonic peeling, etc.), and the broken block and sheet catalyst after peeling is collected and crushed by a crusher. Optionally, an appropriate amount of active component is added, and the low-temperature denitration catalyst is regenerated by, for example, re-coating, thermoplastic, hot pressing, extrusion molding, etc.
[0120] In the low-temperature denitration catalyst prepared by the above coating and molding method, for example, the preferred carrier skeleton is a thermoplastic plastic carrier skeleton. For example, the carrier skeleton can have the same or different thermoplastic material composition as the thermoplastic emulsion (or powder). For example, the carrier skeleton can be metallic or non-metallic. The thermoplastic plastic carrier skeleton preferably has the same plastic composition as the thermoplastic emulsion (or powder), so that it is more convenient and beneficial for subsequent re-molding regeneration process.
[0121] The carrier skeleton can have a shape selected from sheet, flat plate, corrugated plate, cloth, tubular, granular, mesh structure, honeycomb, or porous sponge.
[0122] The coating forming process is suitable for the following thermoplastic plastics as the carrier skeleton: PEEK, PFA, PPS, PTFE, PBT, PEI, PES, PCTFE, ETFE, PAI, PBI, PI, FEP, PPA, PSU, PPSU, PE, PP, fluororubber (FKM), silicone rubber (VMQ), and nylon (PA).
[0123] In the case where the coated and formed plate-type low-temperature denitration catalyst has a carrier skeleton of thermoplastic plastic, the coating forming process can further include: regenerating the deactivated low-temperature SCR catalyst skeleton by washing, crushing, reforming, and then coating the same with an emulsion of the same thermoplastic plastic containing the powder of the SCR catalytically active component, and reprocessing and forming (for example, by drying, curing, and the like).
[0124] In the case where the coated and formed plate-type low-temperature denitration catalyst has a carrier skeleton of non-thermoplastic plastic material, such as metal or non-metal, the coating forming process can further include: peeling off the deactivated catalyst coating layer of the coated and formed plate-type catalyst that has been deactivated (for example, by mechanical peeling, chemical peeling, ultrasonic peeling, and the like), collecting the broken and flaky catalyst after peeling, adding a thermoplastic plastic material after crushing to form a mixed powder, and optionally adding an appropriate amount of active components and / or foaming agents, pore-forming agents, and the like, and reforming by a reforming process other than coating forming, such as, but not limited to, thermoforming, hot pressing, extrusion molding, and the like, to become a low-temperature denitration catalyst that can be regenerated by reforming, and the shape of which is not limited to a plate shape.
[0125] The coating forming process allows the carrier skeleton to have a self-supporting configuration before reforming and after the completion of the coating processing of reforming, thereby allowing the low-temperature SCR catalyst to have a self-supporting configuration without external support within a set working temperature range.
[0126] Regeneration of low-temperature SCR catalysts
[0127] An important inventive concept and key advantage of the present application is that the low-temperature SCR catalyst of the present application can be conveniently regenerated by a reforming process.
[0128] The following describes the regeneration process of the low-temperature SCR catalyst of the present application, taking the PEEK-based low-temperature SCR catalyst of the present application as an example.
[0129] 1) The deactivated (e.g. deactivated due to sulfur poisoning) PEEK-based thermoplastic molded catalyst, optionally first cleaned, e.g. by ultrasonic cleaning to remove surface fly ash and ammonium sulfate salt deposits, dried and then put into a clean crusher for comminution, e.g. after crushing, passed through a 10 mesh sieve to obtain a regenerated powder for remolding.
[0130] 2) The above regenerated powder is mixed with a suitable proportion of a pore former (see previous examples) and then placed in a mold.
[0131] The pore former can be, for example, NaCl, CaSO4, (NH4)2CO3, carbon powder, etc., and the proportion added can be, for example, 10% to 150% by weight of the regenerated powder. An example of the proportion of NaCl added can be, for example, between 50% and 120% by weight of the regenerated powder.
[0132] 3) The mixed powder is put into a cylindrical mold, the mold is sealed with a press and placed in a muffle furnace for heating and thermoplastic molding, and the molding is performed at a heating temperature of 300-320°C, a pressure of 1 MPa to 5 MPa, and for 2-12 hours. If the particles of the regenerated powder are larger, the molding time of the remolding process step can be appropriately extended.
[0133] 4) After thermoplastic molding, the mold is water-cooled / air-cooled to reduce the temperature, and after the temperature is reduced to room temperature, the catalyst is removed from the mold, water-cooled again, and after the temperature is completely reduced to room temperature, it is removed and transferred to a cleaning solution to wash off the pore former. The soaking time in the cleaning solution can be 1-12 hours, and the cleaning solution can be one or more of ammonia, sodium bicarbonate, ammonium carbonate, and trisodium phosphate solution, and the pH of the solution can be maintained at 5-8. After that, punching is performed on a CNC machine tool to obtain a honeycomb-shaped low-temperature SCR catalyst.
[0134] In this regard, those skilled in the art can understand that in the above process step 1), a certain proportion of catalyst powder (e.g. 10% Mn / Ce powder) and / or PEEK powder can be optionally supplemented in the above regenerated powder to make up for possible loss of components and properties. Of course, this is not necessary, and test studies have shown that without supplementing catalyst and / or polymer powder, the low-temperature SCR catalyst of the present application can still be successfully remolded and regenerated without substantially affecting its catalytic performance. Experimental data show that the denitration efficiency of the low-temperature SCR catalyst of the present application after regeneration is comparable to that of existing industrial catalysts, and the activity can be maintained at least 80% or more, as described in detail below.
[0135] Those skilled in the art can understand that the above-mentioned honeycomb-shaped low-temperature SCR catalyst can be reshaped into other shapes, such as a rod-shaped, pellet-shaped low-temperature SCR catalyst, and the like, as needed during reshaping and regeneration, and does not necessarily have to be reshaped into a honeycomb-shaped low-temperature SCR catalyst.
[0136] Those skilled in the art can also understand that the above-mentioned reshaping and regeneration of the low-temperature SCR catalyst can also be performed using other suitable and applicable process methods other than thermoplastic molding, such as, but not limited to, coating molding, hot-press molding, hot-extrusion molding, 3D printing molding, electrostatic spinning molding, cold-extrusion molding, die molding, blow molding, calender molding, rotational molding, vacuum molding (blow molding), casting molding (injection molding), slush molding, flow molding, foaming molding, press injection molding, winding molding, and the like, which can be determined according to the material type of the thermoplastic plastic skeleton, the catalyst active ingredient and parameters, the shape of the low-temperature SCR catalyst required, the needs of the application, and the like.
[0137] Fine SCR DeNOx catalyst system regenerable multiple times and its operation
[0138] Figure 13 An example of a multiple-regenerable fine SCR denitration catalyst system according to an embodiment of the present application is schematically shown for illustratively showing and describing the system of the segmented catalyst (module / segment) arrangement of the present application for fine SCR denitration and its general configuration.
[0139] According to the present embodiment, a low-temperature selective catalytic reduction (SCR) system for flue gas denitration is introduced, which includes the low-temperature SCR catalyst of the present application, such as a catalyst module prepared using a thermoplastic molding and extrusion molding process.
[0140] The fine SCR denitration catalyst system of the present application has better performance in the molding process, catalytic activity, and mechanical strength of the low-temperature SCR catalyst, such as providing higher catalytic activity and better mechanical strength.
[0141] In the present embodiment, the fine SCR denitration catalyst system can be composed of several main parts:
[0142] (1) Catalyst modules suitable for replacement: can include multiple (such as multiple layers) of the regenerable low-temperature SCR denitration catalyst products of the present application, such as plate-shaped, honeycomb-shaped, and / or granular catalysts spaced apart from each other, for providing a segmented / staged low-temperature SCR denitration process, such as below 300°C.
[0143] Preferably, as introduced above, the regenerable low-temperature SCR De-NOx catalyst can include: a thermoplastic plastic formed carrier skeleton; a low-temperature SCR De-NOx catalytically active component compounded in and supported by the carrier skeleton. The fine SCR De-NOx catalyst system is configured to facilitate the removal of the deactivated catalyst module and the replacement of a new catalyst module and / or a regenerated catalyst module, which is a catalyst module obtained by regenerating and reloading the regenerable low-temperature SCR De-NOx catalyst taken out from the deactivated catalyst module after the regeneration of the regenerable low-temperature SCR De-NOx catalyst capable of being regenerated by reshaping the thermoplastic plastic carrier skeleton.
[0144] For example, the plurality of catalyst module segments includes at least two of a plate catalyst module segment, a honeycomb catalyst module segment, and a pellet catalyst module segment.
[0145] According to a preferred example, the segmented catalyst module is arranged in the order of the plate catalyst module segment, the honeycomb catalyst module segment, and the pellet catalyst module segment along the direction of the flue gas flow. In this order, as the flue gas flows through the plate catalyst module segment, the honeycomb catalyst module segment, and the pellet catalyst module segment in sequence, due to the internal structure of the three catalyst module segments, the flow rate of the flue gas naturally and sequentially decreases in this order, thereby sequentially, gradually, and effectively removing, for example, nitrogen oxides (NOx) in the flue gas according to the three catalyst module segments. x ), reducing the content of NOx, and achieving segmented fine De-NOx. x
[0146] (2) Reactor: for accommodating the catalyst module and providing a suitable SCR De-NOx reaction environment.
[0147] The reactor can generally be made of stainless steel (such as 316L or 304) or carbon steel (surface coated with high-temperature resistant anticorrosive coating) and have a cylindrical or cuboid shape with specific dimensions designed according to the flue gas treatment capacity (for example, diameter 2-5 meters, length 5-15 meters). The reactor can be internally provided with multiple layers of catalyst modules (for example, arranged in the order of plate catalyst module, honeycomb catalyst module, and pellet according to the direction of flue gas flow), and the thickness of the catalyst layer can be 300-500 mm or more, and the layer spacing can be 50-100 mm to optimize airflow distribution and reaction efficiency. A homogenizer (such as a flow guide plate or a static mixer) can be configured at the inlet of the reactor to ensure uniform mixing of the flue gas and ammonia gas, and a pressure balancing device can be provided at the outlet to avoid airflow disturbance.
[0148] The reactor can be equipped with a flue gas temperature regulation system (such as a heat exchanger or a heater) to maintain the reaction temperature in the range of, for example, 200-300°C to meet the needs of low-temperature SCR catalysts.
[0149] The reactor can be equipped with temperature sensors (e.g., thermocouples or infrared thermometers) and pressure sensors to monitor the operating conditions in real time and automatically adjust through the control system.
[0150] For example, commercially available reactors include the SCR-EE-LA / UR type produced by Hebei Chengyue Environmental Engineering Co., Ltd., which supports low-temperature denitrification and is designed in a modular manner suitable for boiler flue gas treatment; the double-path vertically arranged reactor produced by Shandong Shoufeng Intelligent Environmental Protection Equipment Co., Ltd., which can be applied to various dust flue gas conditions; the honeycomb catalyst integrated reactor provided by Yuanchen Environmental Protection Technology Co., Ltd., etc.
[0151] (3) Injection system: used to inject reducing agents (e.g., ammonia water or urea solution) into the reactor.
[0152] The injection system can generally include:
[0153] - Ammonia / ammonia water injection system: the nozzle can be made of stainless steel (e.g., 316L) or ceramic, and the structure can be a multi-hole atomizing type or a fan-shaped injection type with a pore size of 0.5-2 mm and an adjustable injection angle of 30-90° to ensure sufficient mixing of ammonia and flue gas. The nozzles can be uniformly distributed along the cross-section of the flue, with a spacing of, for example, 200-500 mm, and the injection direction can be arranged in counter-flow or co-flow with the flue gas flow to enhance the mixing effect. The injection pressure and flow rate of ammonia / ammonia water: working pressure 0.3-0.8 MPa, flow rate range 50-500 L / min (which can be adjusted according to the NOx concentration of the flue gas). x Dynamic adjustment); and
[0154] - Ammonia supply and storage system: which can include a storage tank and a conveying device. The storage tank can be, for example, a stainless steel tank with a volume of 10-50 m 3 , equipped with a liquid level gauge, a safety valve, and a leak detection device, and designed with a pressure of 1.5 MPa. The conveying device can be, for example, a corrosion-resistant centrifugal pump (e.g., Grundfos CR series) or a screw pump with a flow accuracy of ±2% and supporting PLC remote control.
[0155] Examples of commercially available injection systems include, for example, the SNCR-EE-LA / UR type provided by Hebei Chengyue Environmental Engineering Co., Ltd., equipped with high-pressure atomizing nozzles and a redundant safety system; the "double-path ammonia injection system" of Shandong Shoufeng Intelligent Environmental Protection Equipment Co., Ltd. (suitable for high-dust flue gas), etc., which can integrate a steam carrier gas device to enhance the penetration.
[0156] (4) Optional control system: used to monitor and / or adjust the SCR reaction conditions, such as temperature, pressure, and reducing agent injection amount, etc.
[0157] The control system can be used as a component of the fine SCR De-NOx catalyst system, or integrated into the control system of the application site or equipment of the fine SCR De-NOx catalyst system, such as a factory, a workshop, a waste gas treatment section, a ship, a car, etc.
[0158] As an example, the control system can be a PLC (e.g., Siemens S7-1200) based automation system, integrated with an ammonia flow meter (e.g., a mass flow meter), a NO x concentration sensor (e.g., an ultraviolet analyzer), and a temperature feedback module, to achieve closed-loop control of the ammonia to nitrogen molar ratio (NH3 / NO x ) (target value 0.8-1.2). In addition, an ammonia shut-off valve (e.g., an ASCO solenoid valve) can be triggered in an emergency, with a response time <1 second.
[0159] In this embodiment, the general operation of the fine SCR De-NOx catalyst system is as follows:
[0160] (1) System startup: After the system is started, the control system can automatically or manually adjust the reaction condition parameters in the reactor, such as the reaction temperature, pressure, reducing agent injection amount, etc., according to the flue gas conditions.
[0161] (2) SCR catalytic De-NOx reaction: The injection system injects the reducing agent into the reactor, which reacts with the NO x in the flue gas on the surface of the low-temperature SCR catalyst of the present application to generate nitrogen and water.
[0162] (3) Monitoring and adjustment: The control system monitors the reaction efficiency in real time, and adjusts the reaction conditions such as the reaction temperature, pressure, reducing agent injection amount, and / or reaction time, as needed.
[0163] (4) Regeneration of the fine SCR De-NOx catalyst system: After a period of time, or after a predetermined use period, the low-temperature SCR De-NOx catalyst product is removed from the catalyst module, and the low-temperature SCR De-NOx catalyst is subjected to the reshaping regeneration treatment according to the regeneration method of the present application (e.g., the regeneration of the low-temperature SCR catalyst is described above), and the regenerated low-temperature SCR catalyst is reinstalled into the catalyst module, thereby completing the regeneration of the fine SCR De-NOx catalyst system. Thus, the regenerated fine SCR De-NOx catalyst system can be reused and used normally.
[0164] More specifically, according to an example, the recycling method of the regenerated fine SCR De-NOx catalyst system can include the following steps: taking out the deactivated catalyst module from the reactor; pre-treating the low-temperature SCR De-NOx catalyst of the deactivated catalyst module before regeneration; re-shaping the pre-treated low-temperature SCR De-NOx catalyst, and at the same time, regenerating the low-temperature SCR De-NOx catalyst; loading the regenerated low-temperature SCR De-NOx catalyst back into the catalyst module, and then re-loading the catalyst module back into the reactor, thereby recycling the fine SCR De-NOx catalyst system.
[0165] The pre-treatment can include the following steps: crushing the low-temperature SCR De-NOx catalyst of the deactivated catalyst module to obtain regenerated powder within a desired size range. Before or after the crushing, the low-temperature SCR De-NOx catalyst of the deactivated catalyst module can be washed. After the crushing, a screening process can also be performed.
[0166] The regenerated fine SCR De-NOx catalyst system of the present embodiment uses the re-shapeable regenerated low-temperature SCR De-NOx catalyst of the present application, has lower cost, very simple and efficient re-shaping and regeneration process, almost 100% recyclability, almost no loss of catalytic activity, and better mechanical strength than existing catalyst products, which can be effectively recycled for reducing NOx emissions in flue gas x , reducing energy consumption, reducing pollution, reducing waste, re-shaping and recycling, low maintenance cost, light weight of catalyst (module) and convenient installation and transportation, etc., and meets strict environmental protection and regulatory requirements.
[0167] Testing and evaluation of low-temperature SCR catalysts
[0168] Figure 4 A schematic diagram of an activity evaluation device for testing and evaluating the catalytic activity of the honeycomb low-temperature SCR catalyst of the present application is schematically shown. Through the activity evaluation device, the catalytic activity of the honeycomb low-temperature SCR catalyst of the present application, such as the MnO x / CeO2 catalyst component, can be tested and evaluated, wherein the reaction gas can be mixed in the gas mixing tank via the mass flow meter to control the gas flow, and after the catalytic reaction treatment of the low-temperature SCR catalyst of the present application, the flue gas NO x content test can be performed at the tail gas end.
[0169] Figure 5The performance of PEEK catalyst prepared by the thermoplastic molding method according to an embodiment of the present application (i.e., the PEEK-based low-temperature SCR catalyst of the present application) is compared with that of an industrial catalyst. In the test, the test carrier gas is N2, the gas flow rate is 2.1 m / s, NO is 500 ppm, NH3 is 500 ppm, O2 is 5%, and the volume space velocity GHSV is 6000 h-1. -1 The test results of the catalytic activity performance of the PEEK catalyst, the industrial small-scale catalyst, and the industrial catalyst under the same size and the same test conditions are compared. The test results show that the low-temperature SCR catalyst of the present application prepared by using PEEK plastic as the carrier material has high catalytic activity and is close to the performance of the industrial catalyst.
[0170] Figure 6 The performance of PEEK, PFA, and PPS-based catalysts prepared by the thermoplastic molding method according to an embodiment of the present application is compared with that of an industrial catalyst. In the test, the test carrier gas is N2, the gas flow rate is 2.1 m / s, NO is 500 ppm, NH3 is 500 ppm, O2 is 5%, and the volume space velocity GHSV is 6000 h-1. -1 The performance of the catalysts prepared by thermoplastic molding of different materials is compared with that of the industrial catalyst under the same size and the same test conditions. The content in the brackets after the material indicates the mass ratio of the active component of the catalyst in the carrier material. It can be seen that the catalytic performance of the molded catalyst prepared by using PEEK and PFA materials as the base materials is almost the same as that of the industrial catalyst in the temperature range of 150℃ to 200℃.
[0171] Figure 7 The performance of different plastic-based catalysts prepared by the hot-press molding method according to an embodiment of the present application is compared. In the test, the test carrier gas is N2, the gas flow rate is 2.1 m / s, NO is 500 ppm, NH3 is 500 ppm, O2 is 5%, and the volume space velocity GHSV is 1500 h-1. -1 The performance of the plate-type catalyst products of the present application prepared by using three different catalyst skeleton materials is close to that of the industrial catalyst.
[0172] Figure 8 The SO2 poisoning performance test of the PEEK-based catalyst according to an embodiment of the present application and the SO2 poisoning performance test results of the PEEK-based catalyst remolded after use are shown. In the test, the test carrier gas is N2, the gas flow rate is 2.1 m / s, NO is 500 ppm, NH3 is 500 ppm, O2 is 5%, SO2 is 200 ppm, and the volume space velocity GHSV is 9000 h-1. -1In this comparative experiment, the performance of the shaped catalyst prepared with PEEK material was tested under a higher SO2 concentration of 200 ppm. The catalyst activity decreased slightly within 24 h but stabilized at about 80% and did not change any more. After 24 h of testing, the catalyst was taken out and reshaped. The reshaped catalyst was subjected to the same anti-poisoning experiment. The results showed that the catalyst performance remained above 80% and did not decrease in the next 24 h of SO2 poisoning test. This indicates that the reshaping process does not affect the catalyst activity.
[0173] Figure 9 The data of performance recovery of the PEEK-based catalyst after SO2 poisoning and regeneration according to an embodiment of the present application are schematically shown. The data of performance recovery after SO2 poisoning and regeneration and the performance are given.
[0174] Figure 10 The performance test results of the PEEK-based catalyst after multiple reshaping and working at a predetermined reasonable working temperature are schematically shown. A small amount of broken powder is inevitably lost during the reshaping process. Therefore, catalyst powder or thermoplastic powder can be appropriately added during the reshaping process to make the size of the reshaped catalyst and the size before breaking basically consistent. In general, the amount added is preferably less than about 30% of the total catalyst amount before breaking. Excessive amount of active component will result in a smaller specific gravity of the thermoplastic material, a weak bonding effect between the active components, and difficulty in shaping.
[0175] Introduction of some technical effects of low-temperature SCR catalysts
[0176] In the technical content of the present application, the thermoplastic material can be used as a carrier (or matrix, skeleton, carrier skeleton, etc.) material of the catalyst to replace the existing TiO2 and other conventional materials, thereby simplifying the integrated shaping process of the catalyst and the regeneration process (such as through reshaping) of the catalyst. The polymer thermoplastic is used as a carrier material, and the catalyst powder is used as an inorganic binder of the thermoplastic, so that the two are tightly combined during the thermoplastic shaping process, improving the mechanical strength of the overall catalyst and avoiding the leaching of the active component of the catalyst. The addition of the pore-forming agent enables the monolithic catalyst to have more small pore structures during preparation, thereby improving the specific surface area of the catalyst. The use of thermoplastic as a base material enables the catalyst to be reused, and the regeneration process is simple and fast, which can avoid energy waste and environmental pollution in the traditional regeneration process, and greatly prolongs the service life of the catalyst.
[0177] The application is proved by experiments that the catalyst prepared by the preferred formula of the application has similar denitration activity to traditional industrial catalysts under the same size and the same test conditions at 200 DEG C, 150 DEG C and 100 DEG C; under the preferred catalyst formula of the application, the performance of the catalyst remains above 80% without decline under long-time continuous operation at 200 ppm SO2; after the poisoned catalyst is cleaned and reshaped by the regeneration method introduced in the application, the activity of the catalyst remains basically the same as the performance before reshaping under the tests at 200 DEG C, 150 DEG C and 100 DEG C; after the catalyst is reshaped for multiple times by the regeneration method introduced in the application, the activity of the catalyst remains basically the same as the performance before the first reshaping under the tests at 200 DEG C, 150 DEG C and 100 DEG C.
[0178] The foregoing description of several embodiments of the application has been presented for the purpose of illustration. It is not intended to be exhaustive or to limit the application to the precise steps and / or forms disclosed, and obviously many modifications and variations are possible in light of the above teaching. The scope of the application and all equivalents thereof are intended to be defined by the appended claims.
Claims
1. A method of coating a shaped article of a regenerable low-temperature SCR catalyst, the low-temperature SCR catalyst comprising: a carrier skeleton; a low-temperature SCR catalytically active component coating coated on the carrier skeleton of the thermoplastic plastic, the low-temperature SCR catalytically active component coating being formed by a thermoplastic plastic emulsion solidified on the carrier skeleton after coating, wherein the thermoplastic plastic emulsion comprises SCR catalytically active component powders dispersed therein; the method comprises the following steps: (1) adding the SCR catalytically active component powders into the thermoplastic plastic emulsion for stirring and dispersing treatment; (2) coating the thermoplastic plastic emulsion containing the dispersed SCR catalytically active component powders on the carrier skeleton; (3) drying treatment and optional further processing of the coated carrier skeleton to obtain a shaped low-temperature SCR catalyst, wherein the shaped low-temperature SCR catalyst is capable of being regenerated by reshaping.
2. The method of claim 1, wherein, The carrier skeleton is a carrier skeleton of thermoplastic plastic.
3. The method of claim 2, wherein, The thermoplastic plastic of the carrier skeleton has the same plastic composition as the thermoplastic plastic emulsion.
4. The method of claim 1, wherein, The carrier skeleton is a metal carrier skeleton or an inorganic non-metal carrier skeleton.
5. The method according to any one of claims 1-4, characterized in that, The carrier skeleton has at least one shape selected from the group consisting of sheet, flat plate, corrugated plate, cloth, tubular, granular, mesh structure, honeycomb and porous sponge.
6. The method according to any one of claims 1-3, characterized in that, The method is suitable for at least one of the following thermoplastic plastics as the carrier skeleton: PEEK, PFA, PPS, PTFE, PBT, PEI, PES, PCTFE, ETFE, PAI, PBI, PI, FEP, PPA, PSU, PPSU, PE, PP, fluororubber (FKM), silicone rubber (VMQ) and nylon (PA).
7. The method of any one of claims 1-3, wherein, The method further comprises the step of coating the thermoplastic plastic emulsion containing the SCR catalytically active component powders on the carrier skeleton after the deactivated low-temperature SCR catalyst is regenerated by reshaping, so as to regenerate the low-temperature SCR catalyst.
8. The method of claim 7, wherein, The reshaping comprises crushing the deactivated low-temperature SCR catalyst and then reshaping.
9. The method of claim 8, wherein, The reshaping comprises adding thermoplastic plastic powders and at least one of pore-forming agents, foaming agents and plasticizers into the crushed deactivated low-temperature SCR catalyst.
10. The method of claim 4, wherein, The method further comprises: separating the coating layer of the SCR catalytically active component of the deactivated low-temperature SCR catalyst, adding thermoplastic plastic and at least one of pore-forming agents, foaming agents and plasticizers into the coating layer, crushing the mixture to form a regenerated mixed powder; and reshaping the regenerated mixed powder to obtain a regenerated low-temperature SCR catalyst; wherein the reshaping is selected from at least one of the following processes: thermoplastic molding, hot-pressing molding, extrusion molding, 3D printing molding, electrostatic spinning molding, injection molding, die molding, blow molding, calendering molding, rotational molding, suction molding, slush molding, casting molding, flow casting molding, foaming molding, transfer molding and winding molding.
11. The method according to any one of claims 7-10, characterized in that, The carrier skeleton has a self-supporting configuration before reshaping and after reshaping coating processing, so that the low-temperature SCR catalyst has a self-supporting structure without external support in a set working temperature range.
12. The method according to any one of claims 7-10, characterized in that, The method further includes the step of washing the deactivated low-temperature SCR catalyst prior to re-shaping. The method further includes the step of washing the deactivated low-temperature SCR catalyst prior to re-shaping.
Citation Information
Patent Citations
Monolithic low-temperature manganese / cerium honeycomb denitration catalyst
CN117019136A